Bank specific factors, earning and capital management towards loan loss provision: a segregation approach on bank size / Muhamad Sufianhadi Bacho - Bacho, Muhamad Sufianhadi (2019)
Loan loss provision (LLP) is the amount that is provided by the banking institution to cater to loan loss that occurs when the borrower does not make payment on time within 90 days or three months consecutively. LLP is the provision that should be set by Malaysian Banking System (IAS 39 / MFRS 139) and it would be an accrual item that should be done as well. Up until today, there is no specific allotment of LLP. The aim of this research is to determine the impact of earnings management and capital management with the presence of banking specific factor towards tKe loan loss provision (LLP) of the commercial banks via segregation approach on bank size from 2009 to 2017. In order to achieve the objective of this study, Malaysia, Indonesia, Mexico and Panama are the countries that were selected to be tested. The empirical findings based on the Pooled Ordinary Least Square (Pooled OLS) with robust New-west Standard Error for Malaysia, Indonesia and Mexico, and Fixed Effect (FE) with Heteroscedasticity and autocorrelation for Panama recommend that earning management and return on asset have a statistically significant impact on loan loss provisions. The finding of this study found that the proxy of earning management, earning before tax and provision are positively related to loan loss provision. Surprisingly, the variables of capital management are found insignificant in all countries. With respect to the bank specific factor on the loan loss provision for all countries, it revealed that from the overall perspective of the result, the different obvious factor with different country that have really contributed to the loan loss provision are return on asset, total loan, size and loan growth. Based on the findings of segregation approach on bank size, specifically on large bank for all countries, EBTP is the most important indicator to contribute towards the LLP allotment decision.